Strength, stiffness and ductility of masonry infilled frames under lateral loads - Todorov, Koce; Lazarov, Ljupco (Association of Structural Engineers of Serbia, 2018)
Masonry infill is characterized with significant in-plane strength and stiffness and it can greatly alter the response of structures exposed to seismic loads. In order to investigate the influence of masonry infill on the behaviour of structures exposed to lateral loads, an extensive nonlinear static analysis was performed. Six reinforced concrete frames with different number of storey, designed as bare frames were analysed. In the phase of assessment, all structures were updated with the presence of masonry infill panels with two different strength and stiffness characteristics. The obtained results, expressed in terms of the comparison of capacity curves and stiffness degradation shows significant influence of masonry infill on the strength, stiffness and ductility of analased frames.
Keywords: masonry infilled frames, nonlinear static analysis, stiffness degradation